Comparison of the osteogenic effects between two surface interferential stimulation devices to enhance surgically based spinal fusion - Briggs, K. K.; Martinez, S. A.; Smith, L. V.; Carroll, W. J.; Zimmermann, J. A.; Shih, M. S.; Feldman, R.; Lincoln, J. D. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
In human medicine, lumbar spinal fusion procedures for chronic degenerative conditions have significant failure rates leading to the formation of pseudoarthroses. Adjunct procedures including the use of electrical stimulation devices have been developed in animal models, and utilized in human clinical cases, in an attempt to reduce the incidence of nonunion. A randomized, controlled study was performed to compare the effects of two surface interferential stimulation devices (SIS) on a rabbit lumbar spinal fusion model. Twenty-five rabbits underwent bilateral intertransverse process arthrodesis at the L2-L3 disc space. The rabbits were divided into five groups: one control group receiving sham stimulation, and four treatment groups receiving interferential stimulation from one of two devices (RS4i at 13.3 mA, RS4i at 15.8 mA, RS4v at 11.6 mA, and RS4v at 14.8 mA). Dual energy X-ray absorptiometry analyses (DXA) were performed and at 2 week intervals to evaluate fusion site bone mineral density. All rabbits were euthanitized at eight weeks and fusion sites were evaluated for biomechanical strength and histomorphometric properties. There was not any difference in bone mineral density between the groups during the eight week test period. The uniaxial tension tests evaluating maximum load to failure, stiffness, and energy absorbed also resulted in no statistical differences between the groups. The RS4i device at 15.8 mA yielded an increased amount of lamellar bone compared to the control group (p = 0.02). The RS4v device at 11.6 mA resulted in less total bone than the control group (p = 0.04).